Long Noncoding RNA‐1604 Orchestrates Neural Differentiation through the miR‐200c/ZEB Axis. (13th December 2017) - Weng, Rong; Lu, Chenqi; Liu, Xiaoqin; Li, Guoping; Lan, Yuanyuan; Qiao, Jing; Bai, Mingliang; Wang, Zhaojie; Guo, Xudong; Ye, Dan; Jiapaer, Zeyidan; Yang, Yiwei; et al.
Abstract: Clarifying the regulatory mechanisms of embryonic stem cell (ESC) neural differentiation is helpful not only for understanding neural development but also for obtaining high‐quality neural progenitor cells required by stem cell therapy of neurodegenerative diseases. Here, we found that long noncoding RNA 1604 (lncRNA‐1604) was highly expressed in cytoplasm during neural differentiation, and knockdown of lncRNA‐1604 significantly repressed neural differentiation of mouse ESCs both in vitro and in vivo. Bioinformatics prediction and mechanistic analysis revealed that lncRNA‐1604 functioned as a novel competing endogenous RNA of miR‐200c and regulated the core transcription factors ZEB1 and ZEB2 during neural differentiation. Furthermore, we also demonstrated the critical role of miR‐200c and ZEB1/2 in mouse neural differentiation. Either introduction of miR‐200c sponge or overexpression of ZEB1/2 significantly reversed the lncRNA‐1604 knockdown‐induced repression of mouse ESC neural differentiation. Collectively, these findings not only identified a previously unknown role of lncRNA‐1604 and ZEB1/2 but also elucidated a new regulatory lncRNA‐1604/miR‐200c/ZEB axis in neural differentiation. Stem Cells 2018;36:325–336 Abstract : lncRNA‐1604 is required for the neural differentiation process of mouse embryonic stem cells, and functions as a ceRNA of miR‐200c and regulates ZEB1/2 to orchestrate neural differentiation. These findings not only identify an unrevealed role of lncRNA‐1604 and ZEB1/2 but also elucidate a new regulatory pathway of lncRNA‐1604/miR‐200c/ZEB axis in neural differentiation.